Effects of DDGS as a replacement for SBM in Boer grower rations - Wines, Anna R.; Crane, Alison R.; Lattimer, James M.; Jones, Cassandra K. (My University, 2018)
With the U.S. goat industry, up 211%, from 1.25 million head in 2002 to 2.64 million head in 2017, goat producers and the industry are looking for a new cost effective way of feeding. Other research projects have shown great results of feeding DDGS to sheep, but there is very limited data for goat producers to base recommendations for potential inclusion of DDGS in a goat diet. Thus, the objective of this experiment was to evaluate the efficacy of DDGS as a replacement for soybean meal(SBM) in a Boer goat diet. During this 47 day trial, 48 meat goat kids (approximately 70 d of age) were housed at the Kansas State University Sheep and Meat Goat Center with 3 goats per pen and 4 pens per treatment. The goats were separated into one of the four experimental diets: 1) 0% SBM replaced by DDGS; 2) 33% SBM replaced by DDGS; 3) 66% SBM replaced by DDGS; and 4) 100% SBM replaced by DDGS. All four diets were pelleted, which contained roughages, thus no supplemental forage was needed. Goats and feeders were weighed weekly to determine ADG, ADFI, and G:F. At the conclusion of the experiment, two goats out of each pen were taken to a USDA inspected facility to be slaughtered and to collect carcass data. All data was analyzed using the GLIMMIX procedure of SAS with pen serving as the experimental unit and 0.05 as the alpha value. In conclusion, the treatments did not affect(P>0.10) ADG or ADFI, but did impact (P>0.005) G:F. This was due to a linear improvement (P<0.02) in overall ADG and G:F with increasing DDGS. The greatest feed efficiency (P<0.05) was seen in goats fed 66% or 100% of SBM replaced with DDGS compared to those fed 0% or 33% SBM replaced by DDGS. Lastly, there was no impact (P>0.10) of DDGS on hot carcass weight, yield, loin eye area, or fat depth at the 13th rib. In summary, goats can be fed DDGS without detrimental growth or carcass effects.
Keywords: Spring 2018